2017
DOI: 10.1021/acsbiomaterials.7b00176
|View full text |Cite
|
Sign up to set email alerts
|

Freezing-Assisted Gene Delivery Combined with Polyampholyte Nanocarriers

Abstract: Physical methodologies such as electroporation and the gene-gun technology have been widely used for transfection; however, their applicability is limited because they lead to cell damage and low cell viability. Therefore, to address these limitations we developed a new freeze concentration-based gene transfection system that provides enhanced in vitro gene delivery compared to that provided by the commercially available systems. The system employs a facile freeze concentration step, whereby cells are simply f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In our investigation, we found that 10% PLL-SA had remarkably higher adsorption (Figure G–L), and the same phenomenon was also observed for internalization. This is because the adsorption and internalization of proteins into the cells generally have a linear relationship, as the number of particles that adhere to the cell membrane will reflect that of particles being transferred inside the cells, as has been observed in our previous studies. ,,, Overall, this detailed study demonstrated the efficient use of the ice-crystal-based freezing approach to the internalization of proteins with the help of a unique polyampholyte cryoprotectant.…”
Section: Discussionsupporting
confidence: 62%
“…In our investigation, we found that 10% PLL-SA had remarkably higher adsorption (Figure G–L), and the same phenomenon was also observed for internalization. This is because the adsorption and internalization of proteins into the cells generally have a linear relationship, as the number of particles that adhere to the cell membrane will reflect that of particles being transferred inside the cells, as has been observed in our previous studies. ,,, Overall, this detailed study demonstrated the efficient use of the ice-crystal-based freezing approach to the internalization of proteins with the help of a unique polyampholyte cryoprotectant.…”
Section: Discussionsupporting
confidence: 62%
“…7b). Thus, we have reported a simple technique for freeze-thawing that allows macrophages to efficiently ingest antigens [55], introduce genes [56], and perform cell imaging by introducing quantum dots [57]. This method is inexpensive, novel, and does not require special equipment.…”
Section: Freeze Concentrationmentioning
confidence: 99%
“…Polyampholytes including zwitterionic polymers also show promise in several other biomedical applications such as for cell preservation, antibiofouling, and tissue engineering. , These polyelectrolytes contain both cationic and anionic charges in the polymeric backbone. We previously developed new hydrophobic polyampholytes that can form self-assembled nanoparticles and efficiently transfer protein-based materials to the cytosol of cells. These hydrophobic polyampholytes were easily designed by modifying the anionic functional group dodecylsuccinic anhydride (DDSA) and a large amount of succinic anhydride (SA) in ε-poly- l -lysine (PLL), which confers the hydrophobic polyampholytes with an anionic charge. Although hydrophobicity can enhance cell membrane affinity, it is nevertheless difficult to internalize proteins inside cells because of the negatively charged surface potential.…”
Section: Introductionmentioning
confidence: 99%
“…Although hydrophobicity can enhance cell membrane affinity, it is nevertheless difficult to internalize proteins inside cells because of the negatively charged surface potential. Thus, to achieve efficient delivery to cells, we also developed a novel low temperature-based freeze-concentration approach to act as a driving force to internalize materials inside cells efficiently. Freeze concentration is a physicochemical phenomenon wherein water molecules are crystallized into ice so that the solutes present in the system are ejected, which thereby enhances the concentration. The increased concentration occurs across the periphery of the cell membrane resulting in adsorption of solutes.…”
Section: Introductionmentioning
confidence: 99%